Differences in thermal comfort at bus stops with polycarbonate and opaque roofing at Universiti Putra Malaysia, Serdang, Malaysia - Goshayeshi, Danial (2013)
The quality of outdoor and semi-outdoor spaces influences on well-being and performance of people. Among many factors, thermal condition plays significant role in satisfaction of individuals in such spaces. Although the exploring human thermal comfort in outdoor and semi-outdoor spaces, especially in equatorial climatic condition, is vital, the numbers of studies which mainly focus on this context are few. This fact shows the need of evaluating human thermal comfort in hot and humid climate by taking into consideration the objective microclimate factors along with subjective parameters. Bus stops as a semi-outdoor space can greatly affect the thermal comfort of passengers during the day. Among many elements, roofing material of bus stops has profound effects on thermal sensation of individuals. Consequently, a quantitative field study was implemented in this study in order to assessment the human thermal comfort differences between installing Polycarbonate translucent plastic and opaque roofing cover in bus stops of University Putra Malaysia campus and understanding the thermal preferences of users. Hence, the measuring of four principal microclimatic factors (i.e. air temperature,wind speed, mean radiant temperature and relative humidity) together with subjective questionnaire survey were conducted in order to evaluating thermal sensation and thermal preferences of respondents, simultaneously. This study utilized Physiological Equivalent Temperature (PET) as an appropriate thermal index for assessing environmental thermal condition in outdoor and semioutdoor spaces. The results of this study reveal that opaque roofing material provides better thermal condition for passengers both objectively and subjectively comparing Polycarbonate roofing sheets. The average values of air temperature and PET for Polycarbonate roofing material is higher than opaque station but the humidity values for opaque is places in higher level. The results of questionnaire survey revealed that respondents under bus shelter with opaque roofing material felt more comfortable thermal condition than those under Polycarbonate shelter. Also, it is shown that subjective parameters play significant role in human thermal comfort in semi-outdoor spaces, so, it is needed to take into account the subjective factors for the future studies. Furthermore, this study shows that people in Malaysia can tolerate in higher thermal condition comparing those in Europe or Taiwan. Moreover, the result of this study illustrates that shading has a significant effects on thermal satisfaction of people and well-covered spaces provide better thermal environment for users. The findings of this study can be applied in the future design decision-making concerning outdoor and semioutdoor spaces for providing thermally comfortable non-indoor spaces which can be leaded to increasing the usage of such spaces. In conclusion, the findings of this study contribute towards improving the quality of bus stops as semi-outdoor spaces for passengers in Tropical climate of Malaysia for enhancing the quality of life in urban areas